Science education in girls’ high schools: reason and domesticity: Concepción (Chile) 1883-1920 - Inostroza Retamal , Gina (REVISTA DE HISTORIOGRAFÍA (RevHisto), 2023)
The present article aims to identify, using the analytical category of gender, both the form and contents of the incorporation of science in the curriculum and the importance of cabinets in the practical teaching of science in Chile in female secondary education and especially, in the Liceo de Niñas de Concepción between 1900 and 1920. The historical method was used for the analysis of primary and secondary sources from public and private archives. We identified that the education of girls and adolescents in the Girls’ Lyceum of Concepción and other cities, was permeated by discourses on the duty to be traditional feminine, they gave continuity to the sexual division of labor, since they only accessed the study of science in an instrumental way and based on specialization for productive and reproductive functions, that is, all that knowledge that would serve them as future wives and mothers.
Keywords: science-gender; curriculum in high schools; school